Respon dan Sikap Perawat IGD dalam Menangani Klien dengan Percobaan Bunuh Diri dan Self-Harm: Literatur Review - Eva Fatmah; Shanti Wardaningsih (Universitas Faletehan, 2020)
Suicide is the third leading cause of death worldwide. Most of the suicide attempters were taken to the emergency room (ER) of general hospitals for treatment. The response and attitudes of emergency nurses have an important role in determining the success of treatment in patients with suicide attempts and self-harm. The purpose of this study is to determine the response and attitudes of emergency nurses in general hospitals in treating patients with attempted suicide and self-harm. Searching for articles was done through Pubmed, ProQuest, Ebsco and Scopus databases with the keywords